2001
DOI: 10.1037/0012-1649.37.5.620
|View full text |Cite
|
Sign up to set email alerts
|

Causal learning mechanisms in very young children: Two-, three-, and four-year-olds infer causal relations from patterns of variation and covariation.

Abstract: Three studies investigated whether young children make accurate causal inferences on the basis of patterns of variation and covariation. Children were presented with a new causal relation by means of a machine called the "blicket detector." Some objects, but not others, made the machine light up and play music. In the first 2 experiments, children were told that "blickets make the machine go" and were then asked to identify which objects were "blickets." Two-, 3-, and 4-year-old children were shown various pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
399
1
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 420 publications
(414 citation statements)
references
References 42 publications
5
399
1
9
Order By: Relevance
“…If, for instance, a red block activates a toy both when it is placed on the toy by itself and when it is placed on the toy together with a blue block, but the blue block only activates the toy when the red block is also present, preschoolers infer that the red block, not the blue one, makes the toy go. Control conditions established that children's inferences depend on the probability of the outcome given the intervention, not the frequency of the outcome or the number of failed interventions [4]. Several studies have since replicated this finding, showing that across a range of tasks, ages, and content domains, children use the conditional probability of events to make causal judgments ( [5][6][7][8][9]; see [10] for review).…”
Section: Core Epistemic Practicesmentioning
confidence: 80%
“…If, for instance, a red block activates a toy both when it is placed on the toy by itself and when it is placed on the toy together with a blue block, but the blue block only activates the toy when the red block is also present, preschoolers infer that the red block, not the blue one, makes the toy go. Control conditions established that children's inferences depend on the probability of the outcome given the intervention, not the frequency of the outcome or the number of failed interventions [4]. Several studies have since replicated this finding, showing that across a range of tasks, ages, and content domains, children use the conditional probability of events to make causal judgments ( [5][6][7][8][9]; see [10] for review).…”
Section: Core Epistemic Practicesmentioning
confidence: 80%
“…However, studies of children's causal reasoning have focused on deterministic rather than probabilistic causal relations (e.g., Bullock et al, 1982;Gopnik & Sobel, 2000;Gopnik, Sobel, Schulz, & Glymour, 2001;Shultz, 1982;Shultz & Mendelson, 1975). These studies have found that young children are capable of making quite sophisticated causal inferences from deterministic evidence.…”
Section: Tamar Kushnir and Alison Gopnikmentioning
confidence: 99%
“…Study 3 found that older children had difficulties with the original task even when provided with cues to attend to order information. However, 5-year-olds performed successfully in Study 4, in which the causally relevant event was made more salient.Much of the recent research on the development of causal reasoning has emphasized young children's competence with various aspects of causal reasoning (e.g., Corrigan & Denton, 1996;Gopnik, Sobel, Schulz, & Glymour, 2001;Schlottmann, Allen, Linderoth, & Hesketh, 2002). It has been well established that even in infancy children show some type of sensitivity to the causal relationships between events (Leslie, 1982;Oakes, 1994;Oakes & Cohen, 1990) and that children in the preschool years show an appreciation of the causal powers of familiar objects (Bullock, Gelman, & Baillargeon, 1982;Gelman, Bullock, & Meck, 1980) and seem to infer the causal powers of novel objects in principled ways (Shultz, 1982;Shultz & Kestenbaum, 1985).…”
mentioning
confidence: 99%